Radiološka obravnava okužb globokih vratnih prostorov - Šurlan Popović, Katarina (Zdravniški vestnik, 2019)
Despite the wide use of antibiotics today, deep neck space infections still present potentially life threatening conditions. In children, they mostly arise due to perforation of an inflamed lymph node, while in adults the common causes are dental infections and different infections of the neck. Deep neck infections can progress along horizontal and vertical deep neck spaces. The infection may spread to the upper respiratory and digestive tracts, which poses a serious complication. Early recognition and correct diagnosis are therefore essential for establishing a proper treatment plan. The signs of infection are frequently unclear, due to previous use of antibiotics and steroids. Radiological imaging techniques are therefore invaluable in determining the origin of infection, as well as for the evaluation of the spread and transformation from cellulitis to an abscess. The imaging techniques of choice are CT and MR with contrast enhancement and in some cases also the US. The purpose of this article is to present the radiological assessment of deep neck space infections. Infections of individual deep neck spaces are described in more detail, as well as the correct diagnostic procedures. This review article will help the radiologist in practice to recognize deep neck space infection as well as to differentiate between various forms.
Keywords: absces; abscess; computed tomography; infection; okužba; računalniška tomografija